Optimal Control Application in Narcotics Abuse Model by Involving the Number of Deaths - Anwar, Thaibil; Munzir, Said; Tarmizi, Tarmizi; Nurmala, Eka; Sultan, Sultan (Green Publisher Indonesia, 2025)
Illicit drug use is controlled by prevention and treatment. LH Model is the first model of illicit drug use which has been improved for over ten years. In 2012, estimated about 324 million people or about seven percent of the world's population are drug illicit drug users and 183,000 of them die per year because of illicit drug use worldwide and 12.044 people die each year in Indonesia, but there was no death in the LH Model. In this study the model is extended by adding a state of death (D) which forming LHD model. LHD model is fitted with the illicit drug user data of BNN by selecting parameter values that approach the tendencies of the data, after that LHD model is simulated by minimizing the budget for prevention and treatment. Prevention is dominant on unrestricted budget, while treatment is dominant on restricted budget.